Experimental Study on Skin Friction Topology of Wave Leading Edge Airfoil - Du, Hai; Xia, Haoyang; Jiang, Hao; Yang, Zhangyi; Chen, Shuo (Journal of Environmental Accounting and Management, 2026)
As a new passive flow control technology, bionic airfoil leading edge can be used for drag reduction control of aircraft, to achieve low carbon dioxide emission in aircraft in the future. Studies have shown that the wave leading edge can delay the flow separation, and improve the aerodynamic performance of the airfoil at a high angle of attack (AOA). However, due to the difficulty of detailed measurement of the complex flow structure on the wave leading edge airfoil surface, its main flow characteristics and formation mechanism have not been fully understood. Therefore, it is necessary to thoroughly explore the measurement method of complex separation flow structure and the control mechanism of wave leading edge on surface topology. In this paper, the Global Luminescent Oil Film (GLOF) surface friction technique based on optical flow is used to obtain the surface flow structure of wave leading edge airfoil and baseline airfoil (NACA0012). Firstly, the principle of GLOF and the wind tunnel experiment setup are introduced. Then, the skin friction lines are drawn from the global skin friction vector information obtained from the experiment to obtain the skin friction topology. The influence of wave leading edge on surface flow structure is also discussed. The isolated singularities and boundary switching points in the topological structure are identified to verify whether they satisfy the conservation law given by Poincare-Bendixson (P-B) index formula. The results show that, compared with baseline airfoils, the topological structure of the airfoil does not change significantly when the AOA of the airfoil is low. At the large AOA, the wave leading edge airfoil increases the vortex structure of the airfoil surface and inhibits the generation of separation flow, thus delaying the stall. In addition, the surface topology can be drastically changed, and the area of the separation zone can be greatly reduced, thus improving the aerodynamic performance.